Hambatan Guru terhadap Penerapan Standar Penilaian Evaluasi Pendidikan Ranah Afektif di Pesantren Mutiara Quran Pracimantoro - Nurachman, Azhar; Hanani, Hanif; Amin, Ahmad Yasir Al; Kurniyadi, Mahmud Darul (Lembaga Yasin AlSys, 2024)
The challenges faced by teachers in implementing educational assessment standards in the affective domain is an important issue that needs attention. This research aims to understand how teachers implement educational assessment standards in the affective domain at Pesantren Mutiara Quran Pracimantoro. This study uses a descriptive qualitative analysis method with a phenomenological approach to draw conclusions and address issues related to the topic. The results indicate several difficulties encountered by teachers in implementing educational assessment standards. Efforts to enhance the implementation of these standards in the affective domain include comprehensive approaches such as developing teacher skills, increasing awareness about authentic assessment, and training in data collection techniques.